Tlemcen-Touat-Tombouctou : un réseau transsaharien de diffusion du mālikisme (fin viii/xive-xi/xviie siècle) - Elise Voguet (Revue des Mondes Musulmans et de la Méditerranée)
Benefiting from the development of Tlemcen and the rise of Timbuktu, the Touat (in south-west of present-day Algeria) was, from the end of the VIII/XIV century, one of the main stages on the roads linking North Africa (including Mamluk Egypt) to sub-Saharan Africa. The Tlemcen-Touat-Tombouctou axis played a singular role in bringing these Saharan and Sahelian areas into contact with the ‘Abdalwadide's capital, which was, at that time, a major center for the elaboration of Mālikism. It became a way of transmitting knowledge, and contributed to the arrival, in the oases and in the Niger bend, of scholars from this city. It is the links between these three poles in trade circulations, political relations, and especially in the diffusion and implantation of mālikism in the Sahara between the end of the fourteenth and the beginning of the seventeenth century, which are the subject of this contribution